Parameters and their impacts on the temperature distribution and thermal gradient of solid oxide fuel cell. (1st May 2019) - Guk, Erdogan; Venkatesan, Vijay; Babar, Shumaila; Jackson, Lisa; Kim, Jung-Sik
Highlights: Individual parameter contributions to the thermal gradient were revealed. Numeral analysis performed to validate experimental findings. Gas leakage was the most dominant contributor to temperature rise. Electrochemical reaction was the most dominant contributor to thermal gradient. Thermal plot of cell area used as tool for determining heat source. Abstract: The commercialisation potential of Solid Oxide Fuel Cell is hindered due to certain technical issues. One of these is the thermal gradient across the cell structure during its operational period that can deteriorate the system's performance. In this study, a newly developed multi-point thermal sensor is deployed across the cathode to understand the impact of various factors including cell's operating temperature, fuel flow rate and drawing current density on temperature distribution and its stability. Here we report that direct oxidation of hydrogen due to fuel crossover has been the most impactful contributor for the cell's average temperature increment during both open circuit voltage and loading conditions, while electrochemical oxidation of hydrogen is the most impactful contributor for cell temperature gradient during loading. A relationship has been established between the temperature profile of the cell surface and the source of the temperature variation which allows identification of the responsible parameter.